An improved selective culture medium enhances the isolation of Burkholderia pseudomallei from contaminated specimens. - Goodyear, A; Strange, L; Rholl, D; Silisouk, J; Dance, D; Schweizer, H; Dow, S (American Society of Tropical Medicine and Hygiene, 2013)
Burkholderia pseudomallei is a Gram-negative environmental bacterium found in tropical climates that causes melioidosis. Culture remains the diagnostic gold standard, but isolation of B. pseudomallei from heavily contaminated sites, such as fecal specimens, can be difficult. We recently reported that B. pseudomallei is capable of infecting the gastrointestinal tract of mice and suggested that the same may be true in humans. Thus, there is a strong need for new culture techniques to allow for efficient detection of B. pseudomallei in fecal and other specimens. We found that the addition of norfloxacin, ampicillin, and polymyxin B to Ashdown's medium (NAP-A) resulted in increased specificity without affecting the growth of 25 B. pseudomallei strains. Furthermore, recovery of B. pseudomallei from human clinical specimens was not affected by the three additional antibiotics. Therefore, we conclude that NAP-A medium provides a new tool for more sensitive isolation of B. pseudomallei from heavily contaminated sites.